Transformation on the Southern Ukrainian Steppe : Letters and Papers of Johann Cornies, Volume II: 1836-1842. - Dyck, Harvey L. (Tsarist and Soviet Mennonite Studies, 2020)
This book documents the Tsarist Mennonite experience through the papers of Johann Cornies (1789-1848), an ambitious and energetic leader of the Mennonite settlement of Molochna. Cornies' papers offer a widow onto both the Mennonite world, and onto the Tsarist state's relationship with minorities of the frontier.